Brunhilda, Pięć listów do Konstantynopola (Excerpta z Listów austrazyjskich) - Chudzikowska-Wołoszyn, Małgorzata (Vox Patrum, 2025)
In the collection of Austrasian Letters, the reader's attention is drawn to five letters written on behalf of the Austrasian queen Brunhilda. These letters belonged to two separate packages of diplomatic correspondence, which was prepared for the needs of envoys traveling to Constantinople between 585 and 593. The two missions undertaken at that time concerned the rather difficult and at the same time tense political situation that appeared in the relations between the Merovingians and Constantinople from 582. The main aim was to appease the dissatisfaction of the Byzantine emperor Mauricius due to the failure to fulfill earlier obligations, which consisted in actively involving the Franks in the war with the Lombards. The bargaining chip between the courts was Brunhilda's grandson Athanagild, who had been kidnapped to Constantinople. The queen's letters attached to the diplomatic package clearly stand out from the rest of the correspondence. They are distinguished by their personal content and emotional language, which did not correspond to the accepted diplomatic messages and formulas. However, a detailed analysis of Brunhilda's epistles allows us to state that they were an extremely precise and well-thought-out communication tool. The personal expression and emotional scenarios used in them became a kind of tactic aimed at exerting indirect influence on the emperor. The letters confirm not only the queen's thorough education, but also the position and political influence she had at the royal court. The cool political tactics and strategies she implemented also prove her leadership skills and authority.